2017
DOI: 10.1310/hpj5201-17
|View full text |Cite
|
Sign up to set email alerts
|

Updates in Nutrition Support for Critically III Adult Patients

Abstract: Specialized nutrition support is often employed in critically ill patients who are unable to maintain volitional intake. The Society of Critical Care Medicine (SCCM) and American Society for Parenteral and Enteral Nutrition (A.S.P.E.N.) recently updated guidelines for the provision of nutrition support in critically ill patients. The purpose of this review is to summarize key changes from the previous guidelines as they relate to recently published literature, which will aid the hospital pharmacist in optimizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 43 publications
1
12
0
3
Order By: Relevance
“…To date, IL-6, as one of the few immunological parameters, is used to assess nutritional status (malnutrition detection) [ 48 ]. An increase in proinflammatory cytokines (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…To date, IL-6, as one of the few immunological parameters, is used to assess nutritional status (malnutrition detection) [ 48 ]. An increase in proinflammatory cytokines (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study indicate that the implementation of soybean-based IVFEs restriction in cardiac surgical patients reduced incidence of postoperative nosocomial infections. The main goal of nutritional support in postcardiac surgery patients is to maintain an adequate nutritional supply, prevent potential malnutrition and decrease the risk of nosocomial infections (9,10). Despite recent improvements in the application of nutritional support in China, a much higher percentage of nitrogen and lipids is delivered through PN than through EN according to a cross-sectional study (4).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to this results, another studies also reported that < 70% energy provision was associated with significantly higher 30day mortality compared with > 70 % of the target (31.5 vs. 11.1 %, p=0.01) [11], nutritional guideline also showed that permissive, underfeeding enteral energy provisions have reduced hospital mortality compared with targeted feeding [OR = 0.71, 95% CI. 0.50-0.99, p =0.04] [12]. The figure of this cutoff point of EI, 75% is equal to % [(total energy expenditure (TEE) -physical energy expenditure (PEE) / TEE) [13].…”
Section: The Reason Why 75% Of % Tei Is Cutoff Point To Maximize Better Clinical Outcomes In Stroke Patientsmentioning
confidence: 99%